Representative Speech Act in Arabic News Discourse: Study on Aljazeera and Al-Ahram - Muhammad Lukman Arifianto; Hanik Mahliatussikah; Nur Anisah Ridwan; Ibnu Samsul Huda; Iqbal Fathi Izzudin; Nadia Fatchu Ilmi (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
Covid-19 pandemic has caused many pros and cons which are mainly represented in the news in the mass media. Therefore, this study aims to observe how the mass media from Arab countries represent their position towards the Covid-19 pandemic through the news they release. In this study, the data is retrieved from Aljazeera and Al-Ahram. To find out their thoughts and opinions regarding the Covid-19 pandemic, the representative speech act framework presented by Yule (1996) and Searle (1979) is used. Meanwhile, the descriptive-analytical method on that news is relied, starting from providing data, classifying, analyzing, and presenting the results of the analysis. The result shows that there are four types of representative speech acts found in the Arabic news discourse, they are statement of fact, assertion, conclusion, and description. The writers represent their thoughts and opinions by choosing certain verbs or cognate objects, either agreeing or disputing some opinions, as well as citing various news sources or events that are considered valid and credible. Moreover, the comparison of the results from the two news sources did not show a significant difference because the language of these two newspapers is the Modern Standard Arabic (MSA).